Interstitial lung abnormality (ILA) and nonspecific interstitial pneumonia (NSIP) - Hino, Takuya (Eur J Radiol Open, 2021)
This review article aims to address mysteries existing between Interstitial Lung Abnormality (ILA) and Nonspecific Interstitial Pneumonia (NSIP). The concept and definition of ILA are based upon CT scans from multiple large-scale cohort studies, whereas the concept and definition of NSIP originally derived from pathology with evolution to multi-disciplinary diagnosis. NSIP is the diagnosis as Interstitial Lung Disease (ILD) with clinical significance, whereas only a part of subjects with ILA have clinically significant ILD. Eventually, both ILA and NSIP must be understood in the context of chronic fibrosing ILD and progressive ILD, which remains to be further investigated.